Community Behavior Against the Rise of the Covid-19 Pandemic in Anakalang Village - Origenes Umbu Djawa; Nurwijayanti (Universitas STRADA Indonesia, 2023)
Coronavirus Disease (COVID-19) is an infectious disease caused by the Severe Acute Respiratory Syndrome Coronavirus-2 (SARSCoV-2) virus which has clinical signs resembling pneumonia infection (Huang et al., 2020). Behavior is the result of all kinds of experiences and human interactions with their environment which are manifested in the form of knowledge, attitudes and actions. Behavior is an individual's response/reaction to stimuli that come from outside and from within him (Notoatmojo, 2010). Corona virus (Covid 19) is the largest group of viruses in the Nidovirales order. All viruses in the order Nidovirales are nonsegmented positive-sense RNA viruses. The type of research used is a correlational (relationship) analytic design. This study uses an analytical quantitative research approach. Based on the results of data processing using SPSS, it was found that most of the respondents behaved well, namely as many as 23 respondents with a percentage (56.1%) of a total of 41 respondents. the majority of respondents were not at risk of contracting covid-19, namely as many as 28 respondents with a percentage (68.3%) of a total of 41 respondents. Based on the results of the correlation test, namely the relationship between community behavior and the spread of the Covid-19 pandemic, it was found that the value of p = 0.848 so that p <0.05, which means that there is a significant relationship between community behavior and the spread of the Covid-19 pandemic in Anakalang Village, Central Sumba Regency.